HAPS-Antenna On Air - Mohd. Fareq, Abd. Malek, Dr.; Muhammad Ezanuddin, Abdul Aziz; Soh, Ping Jack; Nornikman, Hassan; Nurul Husna, Mat Rus; Mohd Ezral, Baharudin (Malaysian Invention and Design Society (MINDS), 2010)
21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.